2014
DOI: 10.4018/978-1-4666-5872-1.ch010
|View full text |Cite
|
Sign up to set email alerts
|

New Mindsets

Abstract: The authors situate this chapter within the context of contemporary educational leadership where leaders face technical and adaptive challenges that are increasing in complexity and quantity. In many cases, these are challenges for which they could not have been prepared (e.g., new accountability measures). While adult learning and adult developmental theories have been employed widely to support adults' learning and development in other sectors, they are only recently being employed to inform the practice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Distribution practices epitomize existing conceptions of market intelligence dissemination in the marketing literature (e.g., Deshpandé and Zaltman 1982, 1984; Menon and Varadarajan 1992; Moorman, Zaltman, and Deshpandé 1992), as well as how dissemination is described in numerous marketing management and marketing research textbooks (e.g., Burns and Bush 2010; Kotler and Keller 2012; Malhotra 2012). However, the metaphor of market intelligence as an object that can be disseminated across the organization and interpreted consistently by staff is the very archetype of knowledge transfer criticized in the learning and practice literature for being underspecified and highly limited (Drago-Severson and Maslin-Ostrowski 2014; Duguid 2005; Lave and Wenger 1991; Reckwitz 2002). The practice literature has argued that for explicit knowledge to have meaning for a recipient, the recipient must understand the context of that knowledge relative to some shared, previously established understanding of how to interpret it (Duguid 2005).…”
Section: Discussion Of Schema Update Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution practices epitomize existing conceptions of market intelligence dissemination in the marketing literature (e.g., Deshpandé and Zaltman 1982, 1984; Menon and Varadarajan 1992; Moorman, Zaltman, and Deshpandé 1992), as well as how dissemination is described in numerous marketing management and marketing research textbooks (e.g., Burns and Bush 2010; Kotler and Keller 2012; Malhotra 2012). However, the metaphor of market intelligence as an object that can be disseminated across the organization and interpreted consistently by staff is the very archetype of knowledge transfer criticized in the learning and practice literature for being underspecified and highly limited (Drago-Severson and Maslin-Ostrowski 2014; Duguid 2005; Lave and Wenger 1991; Reckwitz 2002). The practice literature has argued that for explicit knowledge to have meaning for a recipient, the recipient must understand the context of that knowledge relative to some shared, previously established understanding of how to interpret it (Duguid 2005).…”
Section: Discussion Of Schema Update Practicesmentioning
confidence: 99%
“…We found that two types of MIDPs used by IDs—empathic learning and experiential learning practices—were effective at changing market schemas. We label both practices as “learning” to reflect their abilities to change (or create) users’ market schemas, paralleling the educational research on learning (Drago-Severson and Maslin-Ostrowski 2014; Lave and Wenger 1991; Mezirow 1994). Regarding the previously discussed schema update practices, IDs often were perplexed as to why end users did not use the disseminated intelligence.…”
Section: Schema Change Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…By attending to a person's way of knowing, we can better facilitate transformational learning-or growth-by shaping "holding environments" (Kegan, 1982, p. 115) to provide supports and challenges. This theory offers ways to understand implicit and explicit life demands, which may call for changes in skills or behaviors (i.e., informational learning) and changes in the way a person organizes or makes sense of reality (i.e., transformational learning) (Drago-Severson, 2004a, 2012Drago-Severson & Maslin-Ostrowski, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%